(untitled) (UK and Ireland Engineering Education Research Network Conference Proceedings 2023, 2024)
Community-based learning and teaching offers engineering students a transformative educational experience that extends beyond textbooks, labs and classrooms by engaging students in co-creation activities with local community as part of their formal learning. By immersing themselves in real-world community contexts, engineering students develop practical skills, cultivate a sense of social responsibility, and become well-rounded professionals prepared to tackle the intricate challenges of our ever-evolving world. Community-based learning and teaching takes engineering education beyond the confines of ‘in-house’ produced project proposal briefs, leads to better opportunities for interdisciplinary learning (beyond engineering ‘subdisciplines’) and more opportunities for creativity and flexibility in how engineering problems are approached and solved. As part of an institution-wide study, in this paper we share specific findings from engineering educators, as well as university-wide engagement professionals and those supporting teaching and learning (24 in total), on the barriers and opportunities to community-based learning and teaching approaches. Using semi-structured interviews, we used thematic analysis to generate a series of themes which aligned with four key beneficiaries within engineering education: academics, students and community partners and university. Our findings reveal the values and expectations, employability benefits and infrastructural considerations to implement this type of learning as part of future-facing and sustainable curricula in engineering. This includes areas such as motivation, role of the community, partnership building, development of leadership skills and networking and financial planning and relationship management. The findings also provide useful context-specific recommendations for educators seeking to develop their own sustainable approaches towards facilitating community-based learning and teaching in engineering disciplines.